Variation and Gradience in Phonetics and Phonology 2009
DOI: 10.1515/9783110219326.71
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the perception of an L2 contrast: A combined phonetic and phonological account

Abstract: The present study argues that variation across listeners in the perception of a non-native contrast is due to two factors: the listener-specic weighting of auditory dimensions and the listener-specic construction of new segmental representations. The interaction of both factors is shown to take place in the perception grammar, which can be modelled within an OT framework. These points are illustrated with the acquisition of the Dutch three-member labiodental contrast [V v f] by German learners of Dutch, focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
4
2
Order By: Relevance
“…On the other hand, the link that we found between retroflexion in speech and perceptual boundary thresholds appears to contrast with findings in existing studies on Mandarin speakers. Chang et al (2013) suggested that deretroflexion in Taiwan Mandarin speakers is linked to a higher degree of tolerance for perceptual ambiguity in retroflexionthis is the opposite of what we found with our participants. However, this difference in our findings could be related to the fact that Chang et al (2013) Taiwan Mandarin.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the link that we found between retroflexion in speech and perceptual boundary thresholds appears to contrast with findings in existing studies on Mandarin speakers. Chang et al (2013) suggested that deretroflexion in Taiwan Mandarin speakers is linked to a higher degree of tolerance for perceptual ambiguity in retroflexionthis is the opposite of what we found with our participants. However, this difference in our findings could be related to the fact that Chang et al (2013) Taiwan Mandarin.…”
Section: Discussioncontrasting
confidence: 99%
“…Chang et al (2013) suggested that deretroflexion in Taiwan Mandarin speakers is linked to a higher degree of tolerance for perceptual ambiguity in retroflexionthis is the opposite of what we found with our participants. However, this difference in our findings could be related to the fact that Chang et al (2013) Taiwan Mandarin. This demonstrates that speech perception tests should take into consideration the unique characteristics of the native language variety of its participants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is frequently attributed to contact with Southern Min, which lacks retroflex consonants (Chuang & Fon, 2010;Kubler, 1985). The use of retroflexion has socio-indexical value; it is associated with higher education levels and distinguishes standardized Mandarin pronunciation from "dialect-accented" Mandarin (Chang et al, 2013).…”
Section: Mandarin Sibilantsmentioning
confidence: 99%
“…As an example, one group of signers could use sideward reduplication of latnouns very frequently while another group could not use it at all, requiring two grammars with fundamentally different rankings of the respective constraints. Future work should investigate such intra-signer variation and possible user types, in order to determine how such variation can be captured with different grammars (for an example from L2 acquisition, seeHamann 2009).…”
mentioning
confidence: 99%